Eurocentrismo no livro didático de História: um estudo enunciativo da argumentação - Freitas, Bárbara de Souza (2024)
Colonization of America is a landmark in history when we think about power relationships stablished among different folks. This process of colonization creates dualities that differs European and non-European, white people and non-white people, colonizer and colonized, civilized and savage. These dualities arise from race concept, which infiltrates this relationship among folks in the colonies and puts European people in evidence, as they are superior to the others. From this process, the eurocentrism concept arises, which means to put the European as center of development, progress, reference in politics, economy and social issues. Thinking about the impacts of this in social relationships and, more specifically, in Education and knowledge built in schools, we study this topic in teaching materials. This work aims to investigate how history textbooks present Eurocentric positions by making an enunciative semantic analysis of argumentation on these teaching materials. We base our work on the Historic Semantics of the Enunciation/Semantics of the Event and we study argumentation as a meaning relation built on enunciation. For us, argumentation is support of positions. Our analysis used concepts from this theory such as enunciative agency, articulation and rewriting, argumentation and argumentativity. Based on these concepts, we outline our analysis procedures, which are, mainly: selection of data by sondage, identification of articulation and rewriting relations; identification of the types of argumentativity that the utterances presented; description of the argumentation and set of the enunciative figures. We made our research corpus with excerpts from the textbooks História 1:Ensino Médio (Vainfas, 2016), Araribá Plus: História (Apolinário, 2018) e História Sociedade e Cidadania 6 (Boulos Júnior, 2018). All these books are from National Didactic Book and Material Program. As the results, we identify that Eurocentric positions from the texbooks presented two kinds of regularities: topic and word classes. Regarding topic, the more frequent topics we saw on our data was European conquer of America and slavery. Regarding word classes, we identify that the textbooks usually used conjunctions and adjectives (mainly presented before nouns) to support Eurocentric positions designed by the social place of historian in enunciations. That made us define these word classes as argumentative strategies of supporting positions that favor European in these teaching materials.